Sobre a composição química em estrelas evoluídas do aglomerado aberto M67 - Oliveira, Gislana Pereira de (2012)
The Galaxy open clusters have a wide variety of physical properties that make them valuable laboratories for studies of stellar and chemical evolution of the Galaxy. In order to better settle these properties we investigate the abundances of a large number of chemical elements in a sample of 27 evolved stars of the open cluster M67 with different evolutionary stages (turn-off, subgiant and giant stars). For such a study we used high-resolution spectra (R 47 000) and high S/N obtained with UVES+FLAMES at VLT/UT2, covering the wavelength interval 4200-10 600 Å. Our spectral analysis is based on the MARCS models of atmosphere and Turbospectrum spectroscopic tool. The oxygen abundances were determined from the [O I] line at 6300 Å. In addition, we have also computed abundances of Si I, Na I, Mg I, Al I, Ca I, Ti I, Co I, Ni I, Zr I, La II and Cr I. The abundances investigated in this work, combined with their stellar parameters, offers an opportunity to determine the level of mixing and convective dilution of evolved stars in M67. Based on the obtained parameters, the abundances of these seem to follow a similar trend to the curve of solar abundances. Additionally, following strategies of other studies have investigated the relative abundances as a function of effective temperature and metallicity, where it was possible to observe an abundance of Na, Al and Si to the stars in the field of giants. A large dispersion from star to star, is observed in the ratios [X / Fe] for the Co, Zr and La, and the absence of Zr and La, in the stars of the turn-off. Comparisons made between our results and other studies in the literature show that values of abundances are in agreement and close to the limits of the errors